2016
DOI: 10.3168/jds.2015-10684
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of intramammary infection status across the dry period from lifetime cow records

Abstract: The dry period is very important for mammary gland health, with the aim not only to cure existing intramammary infections (IMI) but also to prevent new IMI. Although it is known that the dry period is an important time for optimizing udder health, the probability that individual cows will succumb to a new IMI or, if infected, will fail to cure an IMI is not well established. The aim of this study was to investigate whether lifetime cow data, available through routine on-farm milk recording, could be used to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
0
11
0
2
Order By: Relevance
“…Cows were considered healthy (test-day SCC <200,000 cells/mL before and after the dry period), newly infected (new IMI; test-day SCC <200,000 cells/mL before the dry-off and ≥200,000 cells/mL after calving), cured (from an existing IMI; test-day SCC ≥200,000 cells/mL before dry-off and <200,000 cells/mL after calving), or chronically infected (chronic IMI; test-day SCC ≥200,000 cells/mL before and after the dry period). Fauteux et al, 2014;Henderson et al, 2016) and with cured IMI risks obtained via bacteriological culturing of 69.0% (Pantoja et al, 2009a). Still, as the early lactation is notorious for udder infections (Bradley and Green, 2004), the new IMI proportion might be lower and the cured IMI proportion might be higher than portrayed by infection dynamics in this study.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Cows were considered healthy (test-day SCC <200,000 cells/mL before and after the dry period), newly infected (new IMI; test-day SCC <200,000 cells/mL before the dry-off and ≥200,000 cells/mL after calving), cured (from an existing IMI; test-day SCC ≥200,000 cells/mL before dry-off and <200,000 cells/mL after calving), or chronically infected (chronic IMI; test-day SCC ≥200,000 cells/mL before and after the dry period). Fauteux et al, 2014;Henderson et al, 2016) and with cured IMI risks obtained via bacteriological culturing of 69.0% (Pantoja et al, 2009a). Still, as the early lactation is notorious for udder infections (Bradley and Green, 2004), the new IMI proportion might be lower and the cured IMI proportion might be higher than portrayed by infection dynamics in this study.…”
Section: Discussionmentioning
confidence: 48%
“…Thus, additional measures such as decreasing infection pressure during the dry period, preventing bacteria from entering the udder by use of internal teat sealers (Huxley et al, 2002), improving cows' immune status (Sordillo and Streicher, 2002), and culling cows that have limited odds of curing (Østerås et al, 1999) are necessary to control mastitis during the dry period. The new IMI risk was lower than that reported in Canadian, American, and British research, which varied between 19 and 22.4% (Cook et al, 2002;Pantoja et al, 2009a;Fauteux et al, 2014;Henderson et al, 2016) and the 15.7% obtained by Pantoja et al (2009a) via bacteriological culturing. Meanwhile, the cured IMI risk in our study corresponded well to the reported cured IMI risks of 63 to 71.4% using test-day SCC (Pantoja et al, 2009a;Madouasse et al, 2010;Figure 2.…”
Section: Discussionmentioning
confidence: 52%
“…During the dry period of dairy cows, the mammary gland (MG) undergoes physiological and histological changes that affect udder health and milk production of the next lactation [ 1 , 2 , 3 ]. The dry period is also a good opportunity to treat intramammary infections (IMI) acquired during lactation, although it is also a phase of high risk for the development of new intramammary infections (NIMI; [ 4 ]) that can evolve to clinical mastitis (CM) in subsequent lactation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Durante este período ocorre a involução da GM e intensas alterações fisiológicas e histológicas que preparam a glândula para lactação subsequente (HURLEY, 1989;HENDERSON et al, 2016;JENA et al, 2019 Figura 1 -Ilustração esquemática do risco de novas infecções intramamárias em vacas leiteiras durante o ciclo de lactação, e as divisões do período seco de acordo com suas fases: "A" involução ativa, "B" involução completa e "C" lactogênese.…”
Section: Período Secounclassified
“…Durante o período seco (PS) das vacas leiteiras, a glândula mamária (GM) passa por alterações fisiológicas e histológicas que afetam a saúde do úbere e a produção de leite da próxima lactação (HURLEY et al, 1989;HENDERSON et al, 2016;JENA et al, 2019). Por este fato, a secagem é uma ótima oportunidade para tratar IIM existentes, embora também seja um período de alto risco ao desenvolvimento de novas infecções intramamárias (NIIM;…”
Section: Introductionunclassified